Eosinophilic Fasciitis: A Review of Research and Therapeutic Possibilities - Biernikiewicz, Julia; Wilewska, Anna; Pomirski, Bartosz; Pomirska, Agata; Biernikiewicz, Milena; Alabrudziński, Konstanty; Borowiec, Agnieszka; Borowiec, Kinga; Kwaśniewska, Paulina; Graczyk, Patryk (Journal of Education, Health and Sport, 2024)
Introduction Eosinophilic fasciitis (EF) is a rare inflammatory disorder marked by elevated eosinophils in tissues and blood. Patients typically present with symptoms such as skin swelling, pain, and induration, which can be mistaken for other connective tissue diseases. The pathogenesis of EF is not fully understood, though immune and autoimmune mechanisms appear to play significant roles. Diagnosis often involves biopsies, lab analyses, and imaging techniques. Current treatment mainly consists of corticosteroids, but further research is needed to assess various therapeutic strategies. Understanding EF is essential for improving patient outcomes and quality of life. Purpose The purpose of this article is to enhance knowledge of eosinophilic fasciitis by examining its pathogenesis, immune mechanisms, and diagnostic challenges, as well as evaluating current diagnostic criteria and treatments. Given the rarity and complexity of EF, the study also seeks to clarify its differentiation from similar diseases and offer insights into effective therapies for early diagnosis and improved treatment outcomes. Conclusion EF is a rare disease, and its complexity, due to diverse etiologies and variable treatment efficacy, poses significant challenges in clinical practice. In the near future, the publication of new cases and the initiation of clinical trials should contribute to the development of innovative therapeutic strategies and an effective treatment algorithm. Materials and methods: Our review is based on an analysis of material collected in 'Pubmed', 'Google Scholar' and other scientific articles using the keywords: Eosinophilic fasciitis, Shulman, fibrosis, hypergammaglobulinemia, eosinophilia.